Application E-Learning Based on Cloud Computing at the Faculty of Engineering, Batam University - John Friadi; Elly Rumengan; Dodi Putra Yani (Green Publisher Indonesia, 2022)
The development of information technology and the increasingly widespread use of the internet has changed the learning process in higher education, especially during the COVID-19 pandemic, many higher education are conducting distance learning processes by implementing cloud computing-based e-learning. This is also in line with the government's recommendation that we apply health protocols to break the chain of the Covid-19 virus, such as studying and working from home. Batam University, in this case, the engineering faculty, includes those implementing cloud computing-based e-learning for distance learning The purpose of this research is to see how far the implementation of e-learning based on cloud computing according to users, in this case, are lecturers and students of the engineering faculty of Batam University, knowing the readiness of lecturers and students towards the process and products of e-learning itself and satisfaction from the lecturers and students. at the University of Batam at the engineering faculty during the e-learning implementation process. This research method uses a combination of quantitative and qualitative descriptive methods by distributing questionnaires to lecturers and students in the university environment at the engineering faculty which consists of 4 (four) study programs namely mechanical engineering, electrical engineering, civil engineering, and information systems After processing the data using the validity test, reliability test and qualitative analysis, it was obtained that the lecturer respondents agreed with the implementation of cloud computing-based e-learning by 41%, with an average Respondent Achievement Level (TCR) of lecturers of 81.82% in good category. Student respondents' answers strongly agree with the implementation of e-learning based on cloud computing of 44 with an average Student Achievement Level of Respondents (TCR) of 80.47% in good category.